2021
DOI: 10.1152/ajplung.00519.2020
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation contributes to hypoxia-induced inflammation

Abstract: Inflammation is central to the pathogenesis of pulmonary vascular remodeling and pulmonary hypertension (PH). Inflammation precedes remodeling in preclinical models, thus supporting the concept that changes in immunity drive remodeling in PH. Platelets are recognized as mediators of inflammation, but whether platelets contribute to hypoxia-driven inflammation has not been studied. We utilized a murine hypoxia model to test the hypothesis that platelets drive hypoxia-induced inflammation. We evaluated male and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…This hypothesis posits that individual progenitor cells or stem cells, possibly bone marrow derived, may disseminate locally or spread through the circulation to establish the initial focus of adenomyotic lesions if deposited in the myometrium or the endometrial–myometrial interface (EMI). This deposition may result from local trauma or injury since the injured tissues are likely to cause aggregation of platelets, which may recruit the stem cells [ 41 ] and induce hypoxia [ 42 ], increased estrogen production [ 43 ], and hypoxia-induced inflammation [ 44 ]. However, it is unclear as to why and how this injury—the apparent primum movens—occurs.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis posits that individual progenitor cells or stem cells, possibly bone marrow derived, may disseminate locally or spread through the circulation to establish the initial focus of adenomyotic lesions if deposited in the myometrium or the endometrial–myometrial interface (EMI). This deposition may result from local trauma or injury since the injured tissues are likely to cause aggregation of platelets, which may recruit the stem cells [ 41 ] and induce hypoxia [ 42 ], increased estrogen production [ 43 ], and hypoxia-induced inflammation [ 44 ]. However, it is unclear as to why and how this injury—the apparent primum movens—occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Platelet activation as a trigger factor for inflammation. 38 Senchenkova et al showed that Annexin A1 promoted resolution of inflammation by decreasing platelet adhesion, diminishing platelet activation and aggregate velocity. 39
Figure 3 Schematic representation of Annexin A1 in inhibiting inflammation.
…”
Section: Annexin A1mentioning
confidence: 99%
“…Furthermore, intermittent hypoxia itself increases the production of TF by suppressing the protein C anticoagulant pathway in endothelial cells [59]. Enhanced platelet activity and aggregation were also documented under hypoxic conditions [60,61], and the degree of hypoxia was a significant predictor of platelet activation [62]. In contrast, a recent study demonstrated reduced activation of platelet GP IIb-IIIa under hypoxia resulting in an impaired platelet adhesive function [63].…”
Section: Current Knowledge On the Effects Of Osa On Coagulation Fibrmentioning
confidence: 99%